Emotional AI in EFL Classrooms: Redefining Human–Machine Affect in ELT Research at Islamic University - Rachmawati, Dwita Laksmita; Maruf, Nirwanto; Fadhilawati, Dian (Register Journal, 2025)
Emotional Artificial Intelligence (Emotional AI) is reshaping the landscape of language education by offering learners not only cognitive assistance but also emotional support. In Islamic university contexts, where politeness, respect, and affective sensitivity play essential roles in the learning process, the emotional qualities embedded in tools such as ChatGPT present new pedagogical possibilities. This qualitative study investigates the emotional support provided by ChatGPT during English as a Foreign Language (EFL) learning among Islamic university students and examines their perceptions of ChatGPT as an Emotional AI tool in relation to learning enjoyment, self-efficacy, and resilience. The data were collected from 12 EFL students and three lecturers through semi-structured interviews, focus group discussions, and classroom observations. Thematic analysis was employed to identify recurring patterns related to students’ affective experiences and interpretations of ChatGPT’s emotional responses. The findings revealed that students perceived ChatGPT as a reassuring, patient, and non-judgmental companion that reduces anxiety, encourages risk-taking, and supports emotional stability during challenging learning tasks. Students also perceived ChatGPT as enhancing their learning enjoyment, improving their self-efficacy through personalized scaffolding, and strengthening their resilience by promoting a sense of safe failure and continued effort. Despite these benefits, some expressed ambivalence regarding the authenticity of AI-generated empathy and concerns about over-reliance on emotional AI. Overall, the study highlights the dual cognitive–emotional role of ChatGPT in EFL learning and underscores the importance of integrating Emotional AI thoughtfully in Islamic university settings to maximize affective and academic benefits.